2018
DOI: 10.1016/j.foodchem.2017.07.094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-inoculation and sequential inoculation of Tetragenococcus halophilus and Zygosaccharomyces rouxii on soy sauce fermentation

Abstract: The use of Tetragenococcus halophilus and Zygosaccharomyces rouxii as starter cultures is essential for desirable volatiles production during moromi stage of soy sauce fermentation. In this study, the effect of simultaneous and sequential inoculation of cultures in moromi fermentation models, with respect to viability, physicochemical changes, and volatiles formation (using SPME-GC/MS) was investigated. Interestingly, an antagonism was observed as T. halophilus only proliferated (3 log increase) in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 36 publications
5
71
0
Order By: Relevance
“…Microbes, including Tetragenococcus halophilus , Zygosaccharomyces rouxii and Candida versatilis , are always used as the starters in soy sauce fermentation . Thus, different microbe addition experiments supplemented with metabonomic and multivariate data analysis is a rapid and increasing popular strategy to investigate these compounds . However, aroma‐active compounds represent the characteristic flavor of soy sauce and the umami‐taste is the most important feature of soy sauce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbes, including Tetragenococcus halophilus , Zygosaccharomyces rouxii and Candida versatilis , are always used as the starters in soy sauce fermentation . Thus, different microbe addition experiments supplemented with metabonomic and multivariate data analysis is a rapid and increasing popular strategy to investigate these compounds . However, aroma‐active compounds represent the characteristic flavor of soy sauce and the umami‐taste is the most important feature of soy sauce.…”
Section: Introductionmentioning
confidence: 99%
“…18 Thus, different microbe addition experiments supplemented with metabonomic and multivariate data analysis is a rapid and increasing popular strategy to investigate these compounds. [19][20][21][22] However, aromaactive compounds represent the characteristic flavor of soy sauce and the umami-taste is the most important feature of soy sauce. Therefore, the studies on the effect of these microbes on the production of aroma-active or umami-taste compounds were limited.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse fermentation processes employ different raw materials, brine solution concentrations, fermentation and aging periods, and microorganisms' strains, which can affect the organoleptic properties of soy sauce (Gao et al, 2010;Kaneko, Kumazawa, & Nishimura, 2012). In general, two types of soy sauce can be distinguished based on the raw materials used; one is made with equal amounts of soybeans and wheat, and the other is produced by fermenting only soybeans in brine (Devanthi, Linforth, Onyeaka, & Gkatzionis, 2018). In addition, the traditional Chinese-type soy sauce can be classified into high-salt liquid-state fermentation soy sauce and low-salt solid-state fermentation soy sauce according to the different fermentation processes (Feng et al, 2014;Feng, Zhan, Wang, Zhang, & Lin, 2012;Gao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Soy sauce, a condiment, is consumed worldwide due to its intense taste, distinct flavor, and bioactive substances. The quality of soy sauce is related to the raw materials, fermentation pattern, process parameters, and microbes involved during the process . Numerous studies have been conducted in the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of microorganisms to soy sauce depended on the species or genera of microorganisms, as well as the sequence of inoculation for soy‐sauce fortified fermentation . It was confirmed that the inoculation of T. halophilus and Z. rouxii affected the volatile profiles, and lactic acid bacteria also affected the production of cyclotene, furfural, furfuryl alcohol, and methional …”
Section: Introductionmentioning
confidence: 99%